Etika Profesional Konsultan Pajak Dalam Melaksanakan Perannya Sebagai Mitra Wajib Pajak Dan Pemerintah - Arvita, Rizki; Sawarjuwono, Tjiptohadi (E-Jurnal Akuntansi; Vol 30 No 1 (2020)DO - 10.24843/EJA.2020.v30.i01.p07, 2020)
This research aims to analyze and describe the role of tax consultants in the taxation system in Indonesia and the efforts that can be made to maintain the ethics of professionalism of tax consultants as taxpayer partners and the government. This type of research is descriptive qualitative by using secondary data about taxation obtained from internet searches. Data analysis uses qualitative techniques with stages of data collection, data reduction, and taking conclusions. The results stated tax consultants play an important role in the taxation system in Indonesia, namely as a tax component, which is capable of maintaining stability, healthy and dynamic interaction between taxpayers and the government in accordance with tax regulations established by the government. The government as a tax authority needs to intervene in the implementation of the role of tax consultants to ensure that tax consultants comply with the professional code of ethics, so as to increase the role of tax consultants in creating and encouraging taxpayer compliance with Indonesian taxation regulations. Keywords: Tax Consultant; Ethical Code; Professionalism